Hyperferritinemic sepsis secondary to invasive Toxoplasma gondii in a child with untreated HIV - Jesús Domínguez-Rojas; Jackeline Caute-Lara; Patrick Caqui-Vilca; Mario Cruz-Arpi; Carlos Martel-Ramírez; Miguel Quispe-Chipana; Abel Sánchez-Rodríguez; Noé Atamari-Anahui (Permanyer, 2023)
Background: Untreated human immunodeficiency virus (HIV)-immunosuppressed pediatric patients show high morbidity and mortality from opportunistic infections. Limited cases of hyperferritinemic sepsis have been described in patients with toxoplasmosis. Case report: We describe the case of a 13-year-old female patient with a history of untreated HIV who presented with hyperferritinemic sepsis secondary to Toxoplasma gondii infection and Pneumocystis jirovecci pneumonia. She received ventilatory support, inotropic drugs, treatment for opportunistic germs, and high-dose corticosteroids, but with unfavorable evolution. Conclusions: The global approach to sepsis with elevated ferritin guides to using of therapies aimed at neutralizing the severe inflammatory response. A timely diagnosis would allow prompt treatment and minimize complications.